The Effect of Basil Leaves Extract (Ocimum basilicum) on The Triglyceride Level in Atherosclerosis Rats - Atmi, Serly Rahma; Mahata, Liganda Endo; Rahmatini, Rahmatini; Rofinda, Zelly Dia; Ali, Hirowati; Aliska, Gestina; Khaira, Fathiyyatul (Majalah Obat Tradisional, 2025)
Atherosclerosis is the main cause of cardiovascular disease (CVD) characterized by fat accumulation and transformation, inflammation, smooth muscle cell proliferation, and necrotic cell remnants in the tunica intima of blood vessels. Basil leaves are known to contain active biochemical compounds that have the potential to reduce lipids. This is an experimental study that investigated the effect of basil leaves on rat triglyceride levels in atherosclerotic models. This research consisted of five groups of rats that were induced atherosclerosis by partial carotid ligation and a high-fat diet for 7 days. The treatment group was given basil leaves extract ethanol with 100 mg/kgBW, 200 mg/kgBW dose, and simvastatin 1,5mg/rat/day. Examination of triglyceride levels by enzymatic calorimetry GPO-PAP method using Micro Lab 300. The data were analyzed using One-way ANOVA and Post Hoc Bonferroni. The results showed that there was an average decrease in triglyceride levels in rats given basil leaves extract with 100 mg/kg BW dose and indicated that the Ocimum basilicum leaves extract affected triglyceride levels in rats induced by atherosclerosis.